Analisis Prosedur Pemeliharaan dan Temu Kembali Arsip Inaktif untuk Mendukung Efektivitas Pengawasan Arsip di PT KAI Daop 7 Madiun - Muhammad Raihan Cahyonoadi; Ellyn Eka Wahyu (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Appropriate records maintenance and retrieval procedures constitute a fundamental aspect of achieving effective records supervision. This study aims to analyze the procedures for maintaining and retrieving inactive records to support the effectiveness of records supervision at the Document Unit of PT KAI Daop 7 Madiun. The research employed a qualitative approach using a descriptive method. Data were collected through observation, semi-structured interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which consists of four stages: data collection, data reduction, data display, and conclusion drawing and verification. The findings indicate that the procedures for maintaining inactive records have referred to the company's internal guidelines. However, these internal guidelines still contain procedural gaps when compared with the provisions of the National Archives of the Republic of Indonesia (ANRI) Regulation No. 9 of 2018. The identified problems in inactive records maintenance include overfilled archival boxes, the absence of folder/file numbering, inconsistencies between the records inventory, box labels, and box contents, as well as duplicate box numbering, all of which hinder the records retrieval process. The measurement of records supervision effectiveness resulted in a usage rate of 0.006%, an accuracy rate of 1.8%, and an average retrieval time of 1 minute 45 seconds. These findings indicate that the effectiveness of records supervision still needs to be improved and that records management practices require further evaluation through the refinement of procedures in accordance with national archival standards.